Différance Interpretation of Relationship Failure in NIKI Song Lyrics: Interpretasi Perbedaan Kegagalan Hubungan dalam Lirik Lagu NIKI - muhammad dicky; Poppy Febriana (Academia Open, 2025)
General Background: Song lyrics function as cultural texts reflecting emotional experiences and symbolic representations of relationships. Specific Background: NIKI’s The Apartment We Won’t Share depicts romantic separation through narratives of emotional loss, identity change, and relational uncertainty. Knowledge Gap: Prior lyric studies mainly examine emotional themes without exploring unstable meaning formation through Jacques Derrida’s différance perspective. Aims: This study examines representations of relationship failure in NIKI’s lyrics using différance to identify shifting meanings. Results: The analysis shows that relationship failure is portrayed as a continuous process shaped by delayed meaning, lingering memories, and evolving emotional interpretation. Symbols such as the unshared apartment, unborn child, and post-breakup identity reflect prolonged experiences of loss. Binary oppositions including hope versus reality, desire versus necessity, and freedom versus attachment demonstrate unstable interpretations shaped by past relational experiences. Novelty: This study applies différance to interpret romantic separation as ongoing semantic deferral rather than emotional finality. Implications: The findings enrich literary and cultural studies by providing philosophical insight into contemporary song lyrics and expanding understanding of symbolic narrative ambiguity and emotional representation in popular music. Highlights: Romantic Separation Is Portrayed as Ongoing Meaning Reconstruction Rather Than Final Emotional Closure. Symbolic Lyrical Elements Represent Memory Persistence and Identity Uncertainty After Breakup. Binary Oppositions Reveal Continuous Semantic Ambiguity Within Relational Narratives. Keywords: Différance; Song Lyrics Interpretation; Relationship Failure; Derridean Analysis; Symbolic Narrative